La Pintura Infantil como medio de expresión de emociones en los niños de Inicial II de la Escuela de Educación Básica Benjamín Franklin, de la ciudad de Riobamba, periodo 2021 - Vargas Aguinda, Alejandra Yajaira (2022)
ABSTRACT: Children's painting is a didactic strategy that allows the child to express their feelings and emotions when they do not find another way to explain through words, by combining colors, touching, manipulating, feeling shapes and textures, infants experience, develop creativity and imagination, thus acquiring the necessary elements to understand and comprehend the reality that surrounds them in their environment. The objective of this research is to determine the importance of children's painting as a means of expressing emotions in children of Initial II of the Benjamin Franklin School of Basic Education. Methodologically, the research was based on a qualitative research approach, with a non-experimental design, of a bibliographical and cross-sectional type, due to the level it is considered descriptive, carried out with a nonprobabilistic sample made up of five children who receive virtual classes from a said institution; as a technique, direct observation was applied through the zoom platform, as an instrument, the observation sheet aimed at infants and that allowed knowing the context where they develop thanks to the collaboration of the teacher, it was concluded that children's painting it influences the socio-emotional development in infants, this being the reason for teachers and parents to constantly promote activities with the use of painting at home as well as in the educational institution.